Smoking And Quality Of Life After Acute Myocardial Infarction - Esad Pepic (Archives of Global Professionals, 2011)
Objectives: To examine and compare the quality of life (QoL)of patient with Acute Myocardial Infraction and healthyindividuals. Furthermore to investigates the influence oftobacco smoking on QoL of these groups.Material and Methods: A total of 200 subjects were recruitedfor this study, one hundred of these were smokers and restwas non-smokers. Further sub-classification was done on thebasis of the AMI. SF- 36 was used to evaluate the QoL thequality of life among the smokers and non-smokers with andwithout the incidence of AMI. Data analysis was done usingStatistical Package for Social Sciences SPSS version 13 ®.Results: Findings demonstrate a clear relation to the averageQoL scores among smokers and nonsmokers. Non-smokerswere found to have statistically significant differences (SSD) inQoL with and without the incidence of AMI. High Qol score wasobserved among healthy non-smokers. With increasing age ofsmokers, it is seen that there is a decrease in scores on allsubscales of quality of life, and the value difference scores werestatistically significant (p<0.05).Conclusion: Smoking significantly affects the QoL of patientswith AMI. This effect was more pronounced with age. Maritalstatus was found to affecting the physical functioning, vitalityand mental health of the subjects